A night under the stars at Pantai Kekabu, Marang, Terengganu / Farhan Faat … [et al.] - Faat, Farhan; Zulkifli, Amirul Hakim; Mohd Khamis, Nor Farawahidah; Nik Mohd Nor, Nik Mohd Shahril (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Pantai Kekabu is a public beach famous for its vibrant ambiance and immaculate beauty. My family arrived as the sun was setting, a luminous ember fading into the horizon. Excited for the adventure that lay ahead, we slid our toes into the warm, golden sand as we unloaded our belongings and set up our tents. Our tent was arranged in a perfect spot. The smell of the sea and the salty air that carried it lifted our spirits as we unfolded our sleeping bags and established our space. After setting up camp, my youngest son and I decided to take a stroll along the beach before it got dark. As the sky turned into a kaleidoscope of oranges and pinks, we dashed to the shore, where the refreshing waves were waiting to welcome us. We snapped pictures, frozen moments of happiness against the stunning backdrop of the beach, time seemed to fly by.